Additive, electrolyte and battery
By using a specific structured additive A in a lithium -ion battery, the problem of insufficient thermal discharge risks and cycle performance of lithium -ion batteries under high voltage and high temperature conditions is solved, and the effect of significantly improves safety performance and circulatory performance.
Patent Information
- Application Number
- CN202411602082.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-21
AI Technical Summary
Lithium-ion batteries have a risk of thermal runaway under high voltage and high temperature conditions, and the increase in energy density leads to an increase in the load of active substances, reducing the safety factor of the battery.
Adding agent A with a specific structure, including multiple electronic phosphorus atoms and large -ring polyphothexate structures, to improve the safety performance and cycle performance of lithium ion batteries. The additive can improve the high temperature cycle performance and thermal impact performance through the complexation effect and the free radicals, and improve the ion transmission capacity of the diaphragm through the large molecular structure.
It significantly improves the safety performance and cycle performance of lithium-ion batteries, improves high-temperature cycle and rate performance, reduces the risk of thermal runaway, and improves the ion transmission capacity of the separator.
Smart Images

Figure CN119340483A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an additive, an electrolyte and a battery. Background Art
[0002] In recent years, with the continuous development of lithium-ion batteries, safety has become one of the key performance concerns of consumer batteries and power batteries. However, with the increasing demand for fast charging and energy density, the defects in safety performance have continued to magnify, the voltage system has become higher and higher, and the risk of thermal runaway of lithium-ion batteries has increased significantly. In addition, the continuous increase in energy density will lead to an increase in the load of active substances, causing the safety factor of the battery to continue to decline under thermal runaway. Therefore, how to improve the safety performance of lithium-ion batteries without sacrificing their cycle and rate performance has become the current focus of attention and research. Summary of the invention
[0003] Based on the above problems, the present invention provides an additive, an electrolyte and a battery. The addition of the additive of the present invention can significantly improve the safety performance of lithium-ion batteries, and at the same time have excellent cycle performance and rate performance.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] The first aspect of the present invention provides an additive, comprising an additive A having a structural formula as shown in formula (I) and / or formula (II),
[0006]
[0007] In formula (I), R1 and R2 are each independently selected from substituted or unsubstituted C 1-8 Alkoxy, substituted or unsubstituted C 2-5 Alkenyloxy, substituted or unsubstituted C 6-12 One of the aryloxy groups, wherein, when substituted, the substituent used is halogen; the R3 and R4 are each independently selected from O and S; in formula (ⅠⅠ), the R5, R6, R7, and R8 are each independently selected from O, S or do not exist.
[0008] The second aspect of the present invention provides an electrolyte, the electrolyte comprising an additive, a lithium salt and a solvent, the additive being the additive described in the first aspect of the present invention;
[0009] Preferably, the additive further comprises a nitrile additive, and based on the total mass of the electrolyte, the mass content of the additive A is X wt%, the mass content of the nitrile additive is Y wt%, and 1≤X+Y≤8, and / or 0.2≤X / Y≤8 is satisfied;
[0010] Preferably, the nitrile additive includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, hemponitrile, 1,3,6-hexanetrinitrile and glyceroltrinitrile.
[0011] A third aspect of the present invention provides a battery, the battery comprising an electrolyte, a positive electrode, a negative electrode and a separator, the electrolyte being the electrolyte described in the second aspect of the present invention;
[0012] The positive electrode comprises a layered lithium composite oxide, the chemical formula of which is Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.
[0013] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0014] (1) The additive provided by the present invention has a structural formula as shown in formula (I) and / or formula (II), and the additive A contains multiple electron-deficient phosphorus atoms, which can make it have a stronger complexing effect than ordinary phosphate structures. The multi-site adsorption effect can significantly enhance the complexing effect or effect on transition metals, and significantly improve the high-temperature cycle and high-temperature shelf cycle performance under high-voltage systems.
[0015] (2) The additive A provided by the present invention has a structural formula as shown in formula (I) and / or formula (II), and the macrocyclic polyphosphate structure it contains is relatively fast in blocking free radicals, and can preferentially improve thermal runaway. In addition, the phosphorus-containing macromolecules generated at the blocking site can quickly isolate the continuous occurrence of short circuits, and the generated phosphorus-containing macromolecules are extremely stable. After the short-circuit point is covered, the positive and negative electrodes can be completely isolated, thereby preventing further thermal runaway from occurring at the same site, and significantly improving the thermal shock performance.
[0016] (3) The additive A provided by the present invention has a structural formula as shown in formula (I) and / or formula (II), and its macromolecular structure can significantly improve the ion transmission capacity of the diaphragm after entering the gap of the diaphragm, and improve the high-rate charge and discharge performance of the lithium-ion battery.
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] In a safety test environment, the continuous side reaction of the electrolyte will lead to increased heat generation inside the battery, which will further intensify the side reaction. The continuous occurrence of the chain reaction will eventually easily lead to thermal contraction of the diaphragm and a short circuit, thus causing thermal runaway of the lithium-ion battery. In summary, how to improve the safety performance of lithium-ion batteries without sacrificing their cycle and rate performance has become the focus of attention and research.
[0020] Based on the problems existing in the prior art, the first aspect of the present invention provides an additive, wherein the additive comprises an additive A having a structural formula as shown in formula (I) and / or formula (II),
[0021]
[0022] In formula (I), R1 and R2 are each independently selected from substituted or unsubstituted C 1-8 Alkoxy, substituted or unsubstituted C 2-5 Alkenyloxy, substituted or unsubstituted C 6-12 One of the aryloxy groups, wherein, when substituted, the substituent used is halogen; the R3 and R4 are each independently selected from O and S; in formula (ⅠⅠ), the R5, R6, R7, and R8 are each independently selected from O, S or do not exist.
[0023] First, the present invention provides additive A, the structural formula of additive A is as shown in the above formula (I) and / or formula (II), and it contains multiple electron-deficient phosphorus atoms, which can make it have a stronger complexing effect than ordinary phosphate structures. Its multi-site adsorption effect can significantly enhance the complexing effect or effect on transition metals, and significantly improve the high-temperature cycle and high-temperature shelf cycle performance (high-temperature charge and discharge cycle stability and durability) under high-voltage systems.
[0024] Furthermore, the additive A provided by the present invention contains a macrocyclic polyphosphate structure, which has a faster free radical blocking reaction than the ordinary phosphate structure, and can preferentially improve thermal runaway. The macromolecular phosphorus-containing substance generated at the blocking site can quickly isolate the continuous occurrence of short circuits, and the macromolecular phosphorus-containing substance generated is extremely stable. After the short-circuit point is covered, the positive and negative electrodes can be completely isolated, thereby avoiding further thermal runaway from occurring at the same site, and significantly improving thermal shock performance.
[0025] Furthermore, the additive A having a structure as shown in formula (I) and / or formula (II) provided by the additive of the present invention can significantly improve the ion transmission capacity of the diaphragm after its macromolecular structure enters the gap of the diaphragm. The main reason is that the oxygen-rich ring of the macrocyclic polyphosphate structure can increase the transition speed of lithium ions in the diaphragm layer, the polyoxygen ring structure can increase the transition path of lithium ions during the transition process, and the electron-deficient polyoxygen structure can induce rapid transition of lithium ions, accelerate the passage of lithium ions through the diaphragm in the concentration difference region, and reduce the dependence on the transfer of macromolecular solvation structure. Therefore, it can significantly improve the rate performance of lithium ion batteries and improve the cycle stability of lithium ion batteries under high-rate charge and discharge.
[0026] In one embodiment, the additive A comprises at least one of the compounds shown in (A1) to (A6):
[0027]
[0028]
[0029] The second aspect of the present invention provides an electrolyte, the electrolyte comprising an additive, a lithium salt and a solvent, the additive being the additive described in the first aspect of the present invention;
[0030] The additives also include nitrile additives. Based on the total mass of the electrolyte, the mass content of the additive A is X wt%, and the mass content of the nitrile additive is Y wt%, satisfying 1≤X+Y≤8. Exemplarily, the value of X+Y can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8; in a preferred embodiment, 2≤X+Y≤5.
[0031] Furthermore, 0.2≤X / Y≤8 may be satisfied simultaneously or not. For example, the value of X / Y may be 0.2, 0.3, 0.4, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8. In a preferred embodiment, 1≤X / Y≤4.
[0032] In a specific embodiment, the nitrile additive includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, hemponitrile, 1,3,6-hexanetrinitrile (HTCN), and glycerol trinitrile. In a preferred embodiment, the nitrile additive includes 1,3,6-hexanetrinitrile.
[0033] The present invention can significantly improve the safety performance while avoiding the performance degradation caused by insufficient interface protection by controlling the content relationship of additive A and nitrile additives; the main function of additive A is to capture free transition metal ions, and the nitrile additives can protect the active materials by being adsorbed on the surface of the active material, therefore, it is necessary to regulate the mass content relationship of two different types of additives, so as to significantly improve the safety performance while avoiding the performance degradation caused by insufficient interface protection; specifically, when X / Y is greater than 8, the mass content of the nitrile additive is relatively small, which will lead to a significant decrease in the protection ability of the active material, while too much additive A cannot provide the same effect as the nitrile additive, so the high-temperature cycle performance is significantly deteriorated, and the active material particles are severely broken after the cycle; when X / Y is less than 0.2, the mass content of the nitrile additive is excessive, which will lead to a significant increase in the interface impedance of the active material, and the high polarization caused by the high impedance during the cycle will significantly deteriorate the cycle performance and rate performance. Therefore, the performance degradation caused by insufficient interface protection can be avoided by adjusting the ratio X / Y of additive A and nitrile additives; in addition, by adjusting the sum of the mass contents of additive A and nitrile additives at the same time, it is possible to avoid too little use of the two additives, thereby preventing them from playing a role in avoiding thermal runaway and improving rate performance, and to avoid too much total use of the two additives, thereby preventing too many additives from causing an increase in electrolyte viscosity, thereby increasing the internal resistance of the battery and limiting the battery's charge and discharge rate.
[0034] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the additive A is X wt%, satisfying 0.1 wt%≤X wt%≤8 wt%; illustratively, the mass content of the additive A, X wt%, may be 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, or 8 wt%. If the mass content of additive A is too small, the safety performance of the battery cannot be effectively improved; if the mass content of additive A is too large, the impedance will increase, resulting in increased interface polarization, making the positive and negative electrode materials easy to charge and discharge at higher voltages, and the excessive amount of additive A will not significantly improve the protection of the positive electrode material, and will also lead to a decrease in material stability; therefore, it is necessary to avoid excessive or insufficient mass content of additive A of X wt%. In a preferred embodiment, 0.5wt%≤X wt%≤4wt%.
[0035] In a specific embodiment, based on the total mass of the electrolyte, the mass content Y wt% of the nitrile additive satisfies 0.1wt%≤Y wt%≤10%; exemplary, the mass content Y wt% of the nitrile additive can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%. Too much nitrile additive will also increase the impedance and polarization of the battery, leading to deterioration of battery performance; while too little nitrile additive will lead to insufficient protection of the positive electrode interface, which is also likely to cause significant deterioration of battery performance. In a preferred embodiment, 0.5wt%≤Ywt%≤4wt%.
[0036] In a specific embodiment, the additive further comprises a sulfur-containing additive. The sulfur-containing additive added in the present invention, such as 1,3-propane sultone, can enhance the stability of the positive electrode side, improve the storage performance of the battery, and can further improve the storage and cycle performance of the lithium battery by using it in combination with additive A.
[0037] In a specific embodiment, the sulfur-containing additive includes at least one of 1,3-propane sultone and propenyl-1,3-sultone. In a preferred embodiment, the sulfur-containing additive includes 1,3-propane sultone.
[0038] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the sulfur-containing additive is 0.1wt% to 5wt%; illustratively, the mass content of the sulfur-containing additive can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.
[0039] In a specific embodiment, the additive further comprises a lithium borate additive. The lithium borate additive added in the present invention can generate a low-impedance stable interface film at the positive and negative electrodes, effectively improving the long-cycle performance of the lithium-ion battery, and by using it in combination with additive A, it can effectively improve the long-cycle stability of the lithium-ion battery, inhibit the impedance growth during the cycle, and improve the cycle capacity retention rate of the lithium-ion battery.
[0040] In a specific embodiment, the lithium borate additive includes at least one of lithium difluorooxalatoborate, lithium difluorobisoxalatoborate, lithium tetrafluoroborate and lithium bisoxalatoborate. In a preferred embodiment, the lithium borate additive includes lithium difluorooxalatoborate.
[0041] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium borate additive is 0.2wt% to 1.5wt%; illustratively, the mass content of the lithium borate additive can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%.
[0042] In a specific embodiment, the lithium salt further comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide;
[0043] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium salt is 12 wt% to 22 wt%; for example, the mass content of the lithium salt can be 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%.
[0044] In a specific embodiment, the solvent includes carbonate and / or carboxylate and fluorinated 1,2 - diethoxyethane.
[0045] In a specific embodiment, the carbonate includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0046] In a specific embodiment, the carboxylate includes at least one of propyl acetate, n - butyl acetate, isobutyl acetate, n - pentyl acetate, isopentyl acetate, ethyl propionate, n - propyl propionate, methyl butyrate, ethyl butyrate, and n - ethyl butyrate.
[0047] The third aspect of the present invention provides a battery, which includes the electrolyte described in the second aspect of the present invention, a positive electrode, a negative electrode, and a separator;
[0048] The positive electrode contains a layered lithium composite oxide with the chemical formula Li (1+x) Ni y Co z M (1-y-z) O2, where - 0.1 ≤ x ≤ 1; 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and 0 ≤ y + z ≤ 1; where M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0049] In a specific embodiment, the negative electrode contains a carbon - based negative electrode material and / or a silicon - based negative electrode material.
[0050] In a preferred embodiment, the carbon - based negative electrode material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0051] In a preferred embodiment, the silicon - based negative electrode material includes at least one of nano - silicon (Si), silicon oxide (SiO x (0 < x < 2)) and silicon carbide.
[0052] In a specific embodiment, the silicon content in the silicon-based negative electrode material is 3wt% to 80wt%. Exemplarily, the silicon content in the silicon-based negative electrode material can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 50wt%, 60wt%, 70wt%, or 80wt%.
[0053] In a preferred embodiment, the negative electrode comprises a silicon-based negative electrode material. When the additive A of the present invention and the electrolyte comprising the additive A are used in a lithium ion battery whose negative electrode active material comprises a silicon-based negative electrode material, the oxygen-rich ring of the macrocyclic polyphosphate structure contained in the additive A can also increase the transmission rate of lithium ions in the silicon-carbon negative electrode system, thereby effectively improving the interface conductivity of the silicon-doped negative electrode, and further improving the cycle performance and rate performance of the lithium ion battery; at the same time, it can avoid the battery from generating a large amount of heat during the charge and discharge process, thereby effectively improving the high temperature safety performance and rate performance of the silicon-doped lithium ion battery.
[0054] In a specific embodiment, the diaphragm is a polyethylene diaphragm, and the thickness of the diaphragm is 4 μm to 12 μm. Exemplarily, the thickness of the diaphragm can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, or 12 μm.
[0055] In the present invention, the preparation method of the lithium-ion battery is as follows: stacking the prepared positive electrode sheet, separator, and negative electrode sheet in order, ensuring that the separator is between the positive electrode and the negative electrode sheets to play an isolating role, and then obtaining a bare cell without liquid injection by winding; placing the bare cell in an outer packaging foil, injecting the prepared electrolyte into the dried bare cell, and obtaining the desired lithium-ion battery through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0056] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0057] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0058] Example 1
[0059] The lithium ion battery of the present invention is obtained by the following method, see Table 1 for details:
[0060] (1) Preparation of positive electrode
[0061] The positive electrode active materials, layered lithium composite oxide LiCoO4, polyvinylidene fluoride (PVDF), conductive carbon black SP (super P) and carbon nanotubes (CNT), are mixed in a mass ratio of 97.2:1:1.3:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.
[0062] (2) Negative electrode preparation
[0063] Artificial graphite, silicon carbon, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5 and deionized water is added to obtain a negative electrode active material under the action of a vacuum mixer, wherein the mass content of silicon element in the silicon carbon is 30wt%; the negative electrode active material is uniformly coated on both surfaces of a copper foil; the coated copper foil is dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet.
[0064] (3) Preparation of electrolyte
[0065] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / PP / EP are mixed in a mass ratio of 10 / 15 / 55 / 20, and then lithium hexafluorophosphate (LiPF6) with a total mass content of 15wt% based on the total mass content of the electrolyte is quickly added thereto as a lithium salt, and after dissolution, additive A (A1) with a total mass content of Xwt% (Xwt% = 3wt%) based on the total mass content of the electrolyte is added, and other additives, specifically, other additives include: 10wt% of fluoroethylene carbonate (FEC), 2wt% of 1,3-propane sultone (PS), 2wt% of 1,3,6-hexanetrinitrile (HTCN), 0.7wt% of lithium difluorooxalatoborate (LiODFB), and stirred evenly. After passing the moisture and free acid tests, the desired electrolyte is obtained.
[0066] (4) Preparation of batteries
[0067] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator (wherein the adhesion between the separator and the negative electrode sheet prepared above is measured to be 14N / m) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0-4.5V.
[0068] Example 2 Group
[0069] Example 2 was carried out in accordance with Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content X wt % of the additive A added to the electrolyte was changed, as shown in Table 1 for details.
[0070] Example 3 Group
[0071] Example 3 was carried out in accordance with Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content Ywt% of the nitrile additive HTCN added to the electrolyte was changed, as shown in Table 1 for details.
[0072] Example 4 Group
[0073] Example 4 was carried out in accordance with Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content of the ester additive PS added to the electrolyte was changed, as shown in Table 1 for details.
[0074] Example 5 Group
[0075] Example 5 was carried out in accordance with Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content of the lithium borate additive added to the electrolyte was changed, as shown in Table 1 for details.
[0076] Example 6 Group
[0077] Example 6 was carried out in accordance with Example 1, with the only difference being that during the preparation of the electrolyte, the type of additive A added to the electrolyte was changed, as shown in Table 1 for details.
[0078] Example 7
[0079] Example 7 was carried out with reference to Example 1, with the only difference being that the specific selection of the negative electrode active material was changed, specifically artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs), in a mass ratio of 94.5:2.5:1.5:1:0.5, see Table 1 for details.
[0080] Comparative Example 1
[0081] Comparative Example 1 was carried out with reference to Example 1, except that during the preparation of the electrolyte, additive A was not added to the electrolyte, and X wt%=0 wt%, see Table 1 for details.
[0082] Table 1
[0083]
[0084]
[0085] Lithium-ion battery test example
[0086] The lithium ion batteries obtained in the above examples and comparative examples were tested by the following method, and the test results are recorded in Table 2:
[0087] The test methods for performance parameters are as follows:
[0088] (1) Cycle test of lithium-ion batteries at 25°C
[0089] The lithium-ion battery was placed at 25°C, charged at 1C constant current to the upper voltage limit (4.5V), then charged at 4.5V constant voltage to 0.05C, and left to stand for 5 minutes; then discharged at 0.5C constant current to 3V, and left to stand for 5 minutes. This is a charge and discharge cycle. The capacity retention rate / % of the lithium-ion battery after 1000T of charge / discharge was recorded, and the results are recorded in Table 2.
[0090] (2) High temperature cycle test of lithium-ion batteries at 45°C
[0091] The lithium-ion battery was placed at 45°C, charged at a constant current of 1C to the upper voltage limit (4.5V), then charged at a constant voltage of 4.5V to 0.05C, and left to stand for 5 minutes; then discharged at a constant current of 0.5C to 3V, and left to stand for 5 minutes. This is a charge and discharge cycle. The capacity retention rate / % of the lithium-ion battery after 400T of charge / discharge was recorded, and the results are recorded in Table 2.
[0092] (3) Rate charging test of lithium-ion batteries
[0093] The corresponding battery was placed in a constant temperature environment of 25℃, ① left to stand for 10min, ② first discharged to 3.0V with 0.2C, ③ left to stand for 10min, ④ charged to 4.45V at a certain rate, with a cut-off current of 0.02C, ⑤ left to stand for 10min, ⑥ discharged to 3.0V with 0.2C, ⑦ left to stand for 10min. Steps ④ to ⑦ were cycled until all rate charging tests were completed, with a charging rate of 3C, and then the constant current charging ratios of different charging rates were collected, constant current charging ratio = constant current charging capacity ÷ charging capacity × 100%, see Table 2.
[0094] (4) Safety performance of lithium-ion batteries
[0095] Thermal shock performance: Under 25℃ ambient conditions, discharge to 3.0V with a given current of 0.2C; leave for 5 minutes; charge to 4.45V with a charging current of 0.2C. When the cell voltage reaches 4.45V, change to 4.45V constant voltage charging until the charging current is less than or equal to the given cut-off current of 0.05C; after leaving for 1h, put the cell into an oven, and increase the oven temperature to 132±2℃ at a rate of 5±2℃ / min, and keep it for 30 minutes before stopping. A total of 6 groups were tested. The judgment standard was that the cell did not catch fire or explode, which was passed, expressed as the number of tests / the number of passes, see Table 2 for details.
[0096] Table 2
[0097]
[0098] From the analysis of Tables 1 and 2, it can be seen that Example 1 of the present invention can significantly improve the cycle performance under the high voltage system by adding additive A. Compared with Comparative Example 1, the cycle capacity retention rate is significantly improved, and the ion transmission capacity of the diaphragm can be enhanced, and the high-rate charging performance of the lithium-ion battery can be effectively improved.
[0099] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An additive, characterized in that: The additive comprises an additive A having a structural formula as shown in formula (I) and / or formula (II), In formula (I), R1 and R2 are each independently selected from substituted or unsubstituted C 1-8 Alkoxy, substituted or unsubstituted C 2-5 Alkenyloxy, substituted or unsubstituted C 6-12 One of the aryloxy groups, wherein, when substituted, the substituent used is halogen; the R3 and R4 are each independently selected from O and S; in formula (ⅠⅠ), the R5, R6, R7, and R8 are each independently selected from O, S or do not exist.
2. The additive according to claim 1, characterized in that The additive A includes at least one of the compounds shown in (A1) to (A6):
3. An electrolyte, characterized in that: The electrolyte comprises an additive, a lithium salt and a solvent, wherein the additive is the additive according to any one of claims 1 to 2; Preferably, the additive further comprises a nitrile additive, and based on the total mass of the electrolyte, the mass content of the additive A is X wt%, the mass content of the nitrile additive is Y wt%, and 1≤X+Y≤8, and / or 0.2≤X / Y≤8 is satisfied; Preferably, the nitrile additive includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, 1,3,6-hexanetrinitrile and glyceroltrinitrile.
4. The electrolyte according to claim 3, characterized in that Based on the total mass of the electrolyte, the mass content of the additive A is X wt%, satisfying 0.1 wt%≤X wt%≤8 wt%; preferably, 0.5 wt%≤X wt%≤4 wt%; And / or, the mass content of the nitrile additive, Y wt%, satisfies 0.1 wt%≤Y wt%≤10%; preferably, 0.5 wt%≤Y wt%≤4 wt%.
5. The electrolyte according to claim 3, characterized in that The additives also include sulfur-containing additives; Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone and propenyl-1,3-sultone; Preferably, based on the total mass of the electrolyte, the mass content of the sulfur-containing additive is 0.1 wt% to 5 wt%.
6. The electrolyte according to claim 3, characterized in that The additives also include lithium borate additives; Preferably, the lithium borate additive includes at least one of lithium difluorooxalatoborate, lithium difluorobisoxalatoborate, lithium tetrafluoroborate and lithium bisoxalatoborate; Preferably, based on the total mass of the electrolyte, the mass content of the lithium borate additive is 0.2wt% to 1.5wt%.
7. The electrolyte according to claim 3, characterized in that The lithium salt further comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide; Preferably, based on the total mass of the electrolyte, the mass content of the lithium salt is 12wt% to 22wt%; and / or, the solvent comprises carbonate and / or carboxylate and fluorinated 1,2-diethoxyethane; Preferably, the carbonate comprises at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; Preferably, the carboxylic acid ester includes at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate.
8. A battery, characterized in that: The battery comprises an electrolyte, a positive electrode, a negative electrode and a separator, wherein the electrolyte is the electrolyte according to any one of claims 3 to 7; The positive electrode comprises a layered lithium composite oxide, the chemical formula of which is Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.
9. The battery according to claim 8, characterized in that The negative electrode comprises a carbon-based negative electrode material and / or a silicon-based negative electrode material; Preferably, the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon; Preferably, the silicon-based negative electrode material comprises at least one of nano-silicon, silicon oxygen and silicon carbon; the silicon content in the silicon-based negative electrode material is 3wt% to 80wt%.
10. The battery according to claim 8, characterized in that The separator is a polyethylene separator, and the thickness of the separator is 4 μm to 12 μm.
Citation Information
Patent Citations
Non-aqueous electrolyte and lithium ion battery
CN107017432A
High-voltage electrolyte and lithium ion battery containing same
CN111129588A
Lithium ion battery electrolyte and lithium ion battery
CN113130999A
Electrolyte additive, non-aqueous electrolyte and lithium ion battery
CN114552011A
Electrolyte and battery
CN116779967A